A Critical Assessment of Locke’s Theory of Epistemology - Saikh, Asmin (RESEARCH HUB International Multidisciplinary Research Journal, 2022)
The word “knowing” plays a significant role in any philosophical discussion. Philosophy considers it essential to analyse the nature and viability of knowledge before attempting to know anything about anything. Such as, “What is knowledge? How do we learn things? What sources of information are there? have been the focus of many well-known philosophers, and as a result, they have discussed knowledge from a variety of angles. The two philosophical schools of thinking, rationalism and empiricism, have offered diametrically opposed explanations for the origins of knowing. With John Locke’s theory of knowledge serving as the primary example, the purpose of this essay is to describe empiricism as a theory of knowing.